Cohort profile: A Prospective Household cohort study of Influenza, Respiratory syncytial virus and other respiratory pathogens community burden and Transmission dynamics in South Africa, 2016–2018. Issue 6 (23rd July 2021) - Cohen, Cheryl; McMorrow, Meredith L.; Martinson, Neil A.; Kahn, Kathleen; Treurnicht, Florette K.; Moyes, Jocelyn; Mkhencele, Thulisa; Hellferscee, Orienka; Lebina, Limakatso; Moroe, Matebejane; Motlhaoleng, Katlego; Gómez‐Olivé, Francesc Xavier; et al.
Abstract: Purpose: The PHIRST study (Prospective Household cohort study of Influenza, Respiratory Syncytial virus, and other respiratory pathogens community burden and Transmission dynamics in South Africa) aimed to estimate the community burden of influenza and respiratory syncytial virus (RSV) including the incidence of infection, symptomatic fraction, and to assess household transmission. Participants: We enrolled 1684 individuals in 327 randomly selected households in a rural and an urban site over three consecutive influenza and two RSV seasons. A new cohort of households was enrolled each year. Participants were sampled with nasopharyngeal swabs twice‐weekly during the RSV and influenza seasons of the year of enrolment. Serology samples were collected at enrolment and before and after the influenza season annually. Findings to Date: There were 122 113 potential individual follow‐up visits over the 3 years, and participants were interviewed for 105 783 (87%) of these. Out of 105 683 nasopharyngeal swabs, 1258 (1%) and 1026 (1%) tested positive on polymerase chain reaction (PCR) for influenza viruses and RSV, respectively. Over one third of individuals had PCR‐confirmed influenza each year. Overall, there was influenza transmission to 10% of household contacts of an index case. Future Plans: Future planned analyses include analysis of influenza serology results and RSV burden and transmission. Households enrolled in the PHIRST study during 2016–2018 were eligible for inclusion in a study of SARS‐CoV‐2 transmission initiated in July 2020. This study uses similar testing frequency to assess the community burden of SARS‐CoV‐2 infection and the role of asymptomatic infection in virus transmission.